Assessing an impact on perinatal outcome in monochorionic and dichorionic twin pregnancy complicated with discordant fetal growth - K. V. Kostyukov; K. A. Gladkova; O. V. Ionov (IRBIS LLC, 2021)
Introduction. Multifetal pregnancy is associated with an increased risk of perinatal morbidity and mortality. Type of placentation and discordant fetal growth may be risk factors of adverse pregnancy outcomes.Aim: to compare an impact of dichorionic and monochorionic twin pregnancies with symmetric and discordant fetal growth on perinatal outcomes, as well as morbidity and mortality.Materials and Methods. There was conducted a retrospective study of 485 pregnant women and paired 959 newborns. Depending on the type of chorionicity, subjects were stratified into two study groups being further subdivided into based on describing fetal weight discordance. The antenatal period and the neonatal outcome of newborns in groups and subgroups were compared.Results. We analyzed 308 dichorionic and 177 monochorionic twin pregnancies. It was found that neonate discordant growth was observed in 5.4 % and 13.4 % (p < 0.001), respectively. The incidence of assisted reproductive technologies was higher in dichorionic than in monochorionic twins comprising 66.5 and 40.7 % (р < 0.001). Antenatal mortality in monochorionic vs. dichorionic twins was by 8-fold higher. The preterm birth rate in monochorionic vs. dichorionic twins was 74.6 and 62.7% (p = 0.009), respectively. Neonate body weight in monochorionic vs. dichorionic twins was lowered comprising 1991 and 2430 gr. (р < 0.001), respectively. Low Apgar scores were more common for monochorionic twins with discordant body weight. The rate of early neonatal mortality in monochorionic vs. dichorionic twins was 4.4 % vs. 1.5 % (p = 0.009), whereas in dichorionic vs. monochorionic twins with weight discordance it was up to 5.8 and 10.5% (р < 0.001), respectively.Conclusion. Monochorionic twin pregnancy complicated with growth discordance is associated with a higher risk of adverse antenatal period as well as neonatal morbidity and mortality compared to symmetric DCDA twins. Chorionicity and growth discordancy represent important predictors for outcome of twin pregnancy.